Determination of oxidative stress in scaly carp (Cyprinus carpio Linnaeus, 1758) exposed to deltamethrin in different water temperature - San, Ahmet Turan; Yonar, M. Enis (Ege Univ, 2017)
In this study, it was aim to investigate oxidative stress in scaly carp (Cyprinus carpio) exposed to delthamethrin in different temperatures. For this purpose, fish were stocked to six different glass aquarium which was adjusted to 23 degrees C water temperature with adjustable thermostat heaters. After fifteen days adaptation period, temperatures of two aquarium were decreased to 18 degrees C, while temperatures of the other two were increased to 28 degrees C. These groups were exposed to 0.036 mu g/L concentration of deltamethrin for 14 days. At the end of the experimental period, the liver and gills were taken. Malondialdehyde (MDA) level as an indicator of lipid peroxidation, reduced glutathione (GSH) level and glutathione S- transferase (GST) activity were determined in these samples. The MDA levels were increased in the liver and gill of the groups at 18 degrees C and 28 degrees C when compared to the control group. The liver and gill MDA levels of the groups treated deltamethrin simultaneously with the change in temperature were higher than the groups at 18 degrees C and 28 degrees C. This increase was also observed in the group treated deltamethrin at 23 degrees C. The GSH levels and GST activities were decreased in the liver and gill of the groups at 18 degrees C and 28 degrees C when compared to the control group. The GSH level and GST activity of the groups treated deltamethrin simultaneously with the change in temperature were lower than the groups at 18 degrees C and 28 degrees C. This increase was also observed in the group treated deltamethrin at 23 degrees C.
Keywords: Fish; glutathione-S-tranferase; malondialdehyde; oxidative stress; reduced glutathione; temperature